The Effect of Green Accounting, Women on Board, and Carbon Emission Disclosure on Firm Value - Sholikhah, Okta Viola Diya Watus; Putikadea, Insyirah (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study is motivated by the increasing emphasis on sustainability, which has encouraged investors to consider environmental and governance aspects in assessing firm value. The objective of this research is to examine the influence of green accounting, Women on Board, and carbon emission disclosure on firm value in energy sector companies listed on the Indonesia Stock Exchange. The study employs purposive sampling, resulting in a sample of 27 firms with 75 firm-year observations over the period 2022–2024. Given the treatment of outliers at the observation level, the dataset is structured as an unbalanced panel. The analysis is conducted using EViews 13 with a random effects model (REM) in a panel data regression framework. The empirical results indicate that green accounting, Women on Board, and carbon emission disclosure do not have a statistically significant effect on firm value. These findings suggest that environmental and governance-related disclosures have not yet been fully integrated into investors’ valuation decisions in the Indonesian capital market.